2016
DOI: 10.1016/j.jaci.2016.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of omalizumab in patients with atopic dermatitis: A systematic review and meta-analysis

Abstract: Omalizumab has been used to treat patients with atopic dermatitis (AD) with controversial results. 1 Our objective was to perform a systematic review and meta-analysis to investigate the efficacy of omalizumab and the factors associated with better therapeutic results in patients with AD.The search included PubMed, MEDLINE, EmBase, and the Cochrane Library (Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Cochrane Controlled Trials Register, and Health Technology Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 15 publications
(10 reference statements)
0
66
0
2
Order By: Relevance
“…In asthma, there is a dose range for omalizumab from 75‐600 mg, according to serum IgE levels as well as patient body weight. In our cases with high serum IgE levels, a fixed dose of 300 mg may be insufficient for neutralization of free‐serum IgE . Consequently, the cases with high IgE serum levels may take more time to achieve the therapeutic effect.…”
Section: Discussionmentioning
confidence: 92%
“…In asthma, there is a dose range for omalizumab from 75‐600 mg, according to serum IgE levels as well as patient body weight. In our cases with high serum IgE levels, a fixed dose of 300 mg may be insufficient for neutralization of free‐serum IgE . Consequently, the cases with high IgE serum levels may take more time to achieve the therapeutic effect.…”
Section: Discussionmentioning
confidence: 92%
“…A second SR and meta‐analysis evaluated 12 case studies and 1 RCT (103 participants). There was no conclusive evidence of the overall effectiveness of omalizumab (43% ‘excellent’ clinical response, 27% ‘satisfying’ and 30% no change or deterioration) but a preplanned multivariate logistic regression suggested that lower IgE concentrations (< 700 IU/mL) were significantly associated with an ‘excellent’ response compared with higher concentrations (700–5000 IU/mL) (OR = 12.3, 95% CI 2.46–62.5).…”
Section: Systemic Treatmentsmentioning
confidence: 99%
“…A case series of seven patients (aged 6–19 years) with severe AD demonstrated clinical improvement of symptoms after 3 to 6 months of treatment [99]. A recent systematic review, however, stated no concrete evidence of the effectiveness of omalizumab as a treatment for AD [100]. …”
Section: Treatmentmentioning
confidence: 99%